A study of cephalic index and facial index in Visakhapatnam, Andhra Pradesh, India - Kumari, K. Lakshmi; Babu, P. V. S. S. Vijaya; Kumari, P. Kusuma; Nagamani, M. (International Journal of Research in Medical Sciences, 2017)
Background: The description of the human body has been a major concern since ancient times. The use of medical terminology enhances reliability of comparison made between studies from different areas thereby contributing higher level of scientific evidence. Cephalic index is an important parameter in forensic medicine, anthropology and genetics to know the sex and racial differences between individuals. Facial index is useful index for forensic scientists, plastic surgeons and anatomist. The parameters are useful for plastic surgeons during treatment of congenital and traumatic deformities, identification of individuals in medicolegal cases by forensic scientists and identifying craniofacial deformities of genetic syndromes by geneticist. Methods: 170 males and 110 female adults from Visakhapatnam, Andhra Pradesh, India region are included in this study. Anthropometric points for cephalic index were measured by using spreading calipers. Facial index measurements were taken by measuring tape. All measurements were taken in subjects sitting in relaxed condition and subjects head is in anatomical position. Cranial index and facial index were calculated as per the formula. Results: Maximum number of males with mean cephalic index values of 80.21 were observed as mesocephalic and female with mean value of 79.25 observed as brachycephalic. Regarding facial index males were leptoprosopic and females were mesoprosopic. Conclusion: Cephalic index and facial index were terms used by anthropologists, anatomists, plastic surgeons and forensic scientists to identify individual’s race and sex for treatment of craniofacial deformities.